Analisis Karakteristik dan Penanganan Kebutuhan Ruang Parkir Sepeda Motor Di Kampus Uniska MAB Banjarmasin - Perdana, Muhammad Gunawan; Ramadani, Hari Nukta (Jurnal Teknik Sipil, 2018)
Universitas Islam Kalimantan (Uniska) Muhammad Arsyad Al Banjari Banjarmasin is one of the oldest private universities in Kalimantan. Uniska has nine faculties and two graduate programs. The increased of students number is 3.11% per each year. With this increased, will automatically increase the need for motorcycle parking in the campus Uniska Banjarmasin, so it takes adequate motorcycle parking space. This condition raises the need to identify the characteristics and handling of motorcycle parking space requirements. The survey method used is the survey technique of parking of the cordon, while the method of data analysis using Hobbs formula 1995 and the formula approach Z by Pignataro 1973. Parking planning refers to the guidelines of the Directorate General of Land Transportation 1996. The need for motorcycle parking space according to the approach of Z formula of 1276 SRP with the assumption of parking duration of 350 minutes and the rate of change of parking is 2 times a day, thus exceeding the static capacity of only 940 SRP. With the data of the growth of the number of students per year, the description of the need for motorcycle parking space for the next 5 years is 1487 SRP. The conclution is the actual parking area unable to fullfill the existing parking space requirements. An alternative solution to this problem solving is through improved management of existing parking area arrangements and the addition of new parking spaces